EVALUATING THE EFFICACY OF CONTAINER TYPES AND SIZES FOR SWEET POTATO CONTAINER CULTIVATION FOR URBAN GARDENING - Abimbola, O. O.; Alfonso, O. C.; Ejalonibu, M. S.; Salawu, I. A.; Gbadegesin, R. O.; Afuape, S.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was conducted at National Root Crops Research Institute (NRCRI), Iresi Sub-Station, Osun State during 2024 and 2025 rainy seasons to evaluate the effects of container type and soil volume on the vegetative growth and root yield of two sweet potato varieties. The treatments consisted of two (2) container types (bucket and sack), three (3) soil volumes (5, 10 and 15 L) and two (2) varieties of sweet potato (Ex-Igbariam and Mothers Delight), these were factorially combined and laid out in a randomized complete block design replicated three times. Data were collected on vine length, number of leaves, and number of branches at 6–14 weeks after planting. Others were marketable and unmarketable root yields assessed at harvest. Results indicated that, soil volume was the primary determinant of vegetative growth and marketable root yield, with larger containers consistently enhancing canopy development and yield. Container type had minimal influence when soil volume was held constant, and increased soil volume did not increase unmarketable yield. Varietal differences were observed in growth dynamics and yield response to soil volume, while treatment effects were generally stable across seasons. The study demonstrates that adequate soil volume, rather than container material, is critical for efficient sweet potato production in container-based systems. These results provide practical guidance for urban growers, supporting the use of low-cost containers combined with sufficient soil volume to optimize sweet potato productivity in space-limited environments.